Increasing frequency capability of PMSM vector controlled drive for pumped storage - Ducar, Ioan; Marinescu, Corneliu (2014 International Conference on Applied and Theoretical Electricity (ICATE), 2014)
The subject of this paper is a comparative study between two supply modes of a permanent magnet synchronous motor (PMSM). The goal is to obtain a better efficiency for a hydraulic pump drive system. The machine (PMSM) is operated in vector control mode. The inverter is controlled with a sinusoidal pulse-width modulation (SPWM) technique. The study will allow to increase the root mean square (RMS) of the voltage and hence speed, avoiding over-modulation. The comparison is also made between third harmonic injection and over-modulation.